Evaluation of the professional teaching competence: chinese experience - Zhernovnykova, Oksana; Kovalenko, Oksana; Mkrtichian, Oksana; Zelenska, Liudmyla (Journal of Education, Health and Sport, 2020)
The article describes the rules and procedures for hiring and evaluating the professional competence of teachers on the example ofChina, where there is a system for evaluating the professional competence of teachers.